Bojana Cvejić: Open work in music. Boulez/Stockhausen/Cage: Cvejić Bojana: Otvoreno delo u muzici. Boulez/Stockhausen/Cage, Studentski kulturni centar, edicija 'Muzika', Beograd, 2004 (MUZIKOLOGIJA-MUSICOLOGY, 2025)
Book Review